The impact of self-directed learning experience and course experience on learning satisfaction of university students in blended learning environments: the mediating role of deep and surface learning approach - Hua, Meng; Wang, Lin; Li, Jun (Frontiers in Psychology, 2024)
Introduction With the rapid development of technology and the evolution of educational ideas, the blended learning model has become the new norm in higher education. Therefore, based on Biggs’ learning process theory, this study aims to investigate the relationships between learning experience, learning approaches, and learning satisfaction of university students within the Chinese blended learning context to explore the dynamic process and mechanism of blended learning. Methods The Chinese modified versions of the Self-Rating Scale of Self-Directed Learning, the Course Experience Questionnaire, and the Revised Study Process Questionnaire were administered to 939 Chinese university first-grade students (444 men, 495 women). The data were analyzed by using the covariance-based structural equation modeling (CB-SEM) technique. Results The results demonstrated that, among Chinese university students, there were significant correlations between the self-directed learning experience, the course experience, the deep learning approach, the surface learning approach, and learning satisfaction. Additionally, the learning approaches mediated the association between the self-directed learning experience and learning satisfaction and between the course experience and learning satisfaction. Conclusion This study provides insight into the facilitative effect of university students’ self-directed learning experience and course experience on their learning satisfaction and how this effect is triggered through the mediating role of different learning approaches with the blended learning context. This study shows the learning behaviors and psychology in a blended learning environment, thus revealing the new learning characteristics of university students by integrating the self-learning characteristics of blended learning into the framework of learning process theory. The findings contribute to assisting blended learning providers in delivering targeted interventions to enhance students’ learning satisfaction.